Revocatoria de las medidas de protección en contravenciones de violencia intrafamiliar y derecho a la integridad de la víctima. - Villa Escudero, Jessica Viviana (2022)
This research work is based on the study of national and international norms and case analysis, with the purpose of determining that the revocation of protection measures violates the integrity of the victim. By virtue of the fact that personal integrity in every dimension constitutes a human right linked to human dignity, i.e., no one should be subjected to undignified treatment of any kind. The Constitution of the Republic of Ecuador recognizes the protection of victims of criminal offenses, which includes protection from any intimidation or threat, as well as the guarantee of non-repetition. Taking into account that the revocation of a protection measure would expose the victim to further exposure to violent events of greater intensity. Considering, in addition, that the Organic Integral Penal Code does not provide specific regulations for cases of violence contraventions with respect to the subject matter. The research is composed of three units: the first one called intra-family violence; the second one called right to integrity; and finally, protection measures in intra-family violence. As for the methodology, it is added, that it was successful in order to meet the objectives and reach the conclusions and recommendations of this work.